Superior Heat Resilient Features for Physiological, Biochemical, Behavioral, Molecular, Neuroendocrine and Epigenetic Adaptation in Tharparkar Cattle - Yadav, Nistha; Rao, Prateek; Sreekumar, Damodaran; Pannu, Urmila (Research Perspective on Biological Science Vol. 4, 2025)
In the context of changing climate conditions, heat stress has emerged as a significant challenge for the dairy industry. Ensuring an appropriate microclimate in animal housing characterised by adequate air circulation, optimal temperature, humidity control, low pollution levels, and minimal gas concentrations has become a primary concern. These elements are crucial for the proper development and maintenance of cow comfort, which in turn supports food security based on livestock. The draft is prepared by considering the changing environmental conditions and the consequent adaptive features of the Tharparkar cattle. According to the Global Climate Risk Index of 2019, India ranks fifth, with extreme heat posing potentially lethal consequences of climate change. Dairy cattle experience heat stress when the temperature-humidity index (THI) exceeds 72. The threshold for heat tolerance varies based on genotype and production levels, with animals at higher production levels being more susceptible to heat stress. Crossbred cattle, such as Karan Fries, exhibit greater metabolic heat production, methane emission, energy loss, and physiological responses compared to zebu cattle. The lower metabolic rate of zebu breeds suggests a superior adaptability to tropical climate regarding heat and methane production. Tharparkar demonstrates superior heat stress tolerance and thermoregulatory responses for providing thermotolerance against heat stress, facilitated by the expression of a highly conserved family of proteins known as heat shock proteins (HSPs). However, despite these thermoregulatory mechanisms, the productivity of zebu cattle, particularly Tharparkar, is significantly hindered in comparison to other indigenous and crossbred cattle.